1994
DOI: 10.1007/bf02244748
|View full text |Cite
|
Sign up to set email alerts
|

PET studies of the uptake of (S)- and (R)-[11C]nicotine in the human brain: difficulties in visualizing specific receptor binding in vivo

Abstract: (S)- and (R)-[11C]nicotine were synthesized by methylation of (S)- and (R)-nornicotine using [11C]methyl iodide. Following their intravenous injection in tracer doses to smoking and nonsmoking healthy males the radioactivity in arterial blood showed a sharp peak at about 1 min followed by a plateau level for the remaining 50 min of recording. Uptake in the brain, as measured by positron emission tomography (PET), was rapid with a peak at 5 min followed by a steady decline towards the end of the measurement. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
46
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 36 publications
8
46
0
1
Order By: Relevance
“…In this study, the maximal boost in arterial concentration of nicotine was determined to be 27 ng/mL (167 nM). Assuming the V T value for the entire brain as 2.6 [3.0 and 2.2 for gray and white matter, respectively (23)], the boost in total brain nicotine concentration was calculated to be 434 nM. Overall, the good agreement between this value and that obtained in the present study (357 nM) verifies the validity of our approach and our assumptions.…”
Section: Maximal Values Of Brain Nicotine Concentration During Cigarettesupporting
confidence: 40%
“…In this study, the maximal boost in arterial concentration of nicotine was determined to be 27 ng/mL (167 nM). Assuming the V T value for the entire brain as 2.6 [3.0 and 2.2 for gray and white matter, respectively (23)], the boost in total brain nicotine concentration was calculated to be 434 nM. Overall, the good agreement between this value and that obtained in the present study (357 nM) verifies the validity of our approach and our assumptions.…”
Section: Maximal Values Of Brain Nicotine Concentration During Cigarettesupporting
confidence: 40%
“…Radioligands developed for noninvasive in vivo imaging of ␣-bungarotoxin-insensitive nAChRs have exhibited shortcomings, such as poor subtype selectivity and high levels of nonspecific binding (Nybä ck et al, 1994 (Flores et al, 1996;Xiao et al, 1998). In contrast to ␣4␤2 nAChRs, nAChRs containing ␣3 and ␤4 subunits, possibly in combination with ␣5 subunits, are distributed mostly in the peripheral nervous system and adrenal glands (Holladay et al, 1997).…”
supporting
confidence: 41%
“…Therefore, the metabolism of nicotine to nornicotine would be a relatively minor pathway in the systemic clearance of nicotine. However, experimental animal studies revealed that nornicotine is present in brain at significant levels (approximately 20% of the total amount of nicotine and its metabolites) (Nordberg et al, 1989;Plowchalk et al, 1992;Nyback et al, 1994;Crooks et al, 1997). The nornicotine concentration in brain was nearly equal to that of nicotine (Crooks et al, 1997).…”
mentioning
confidence: 48%